Agrobacterium-mediated Transformation of Mungbean [Vigna radiata (L.) Wilczek] - SURANINPONG, Potjamarn; CHANPRAME, Sontichai; CHO, Hyeon-JE; WIDHOLM, Jack M. M; WARANYUWAT, Aree (Walailak Journal of Science and Technology (WJST), 2011)
Plasmid pCAMBIA 1301-choA was transformed into Agrobacterium rhizogenes strain K599 and A. tumefaciens strain EHA 105 for mungbean transformation. Cotyledons from different ages of mungbean seedlings were inoculated with both bacteria. The two-day-old cotyledons that were co-cultured with hairy root bacteria showed higher ability to produce branched roots than the others. An average of 10 branched roots was formed on both the wounded abaxial site and the hypocotyl cut end. Ten of 75 individual lines (13.25%) showed GUS positive. In addition, cotyledons that were cut and cultured on MB medium supplemented with 2 mgml-1 BAP for 4 days before co-culture with A. tumefaciens using hairy root method revealed high transformation ability (31.25%). It was found that seed age, cultivar, co-culture conditions and culture conditions were important factors affecting the transformation efficiency.